2008
DOI: 10.1038/mt.2008.160
|View full text |Cite
|
Sign up to set email alerts
|

Dual Therapeutic Effects of Interferon-α Gene Therapy in a Rat Hepatocellular Carcinoma Model With Liver Cirrhosis

Abstract: Human hepatocellular carcinoma (HCC) often arises from a background of liver cirrhosis. Therefore, in order to develop therapeutic strategies for HCC, an animal model bearing multifocal liver tumors accompanied by liver cirrhosis is a preferred experimental setting. In this study, we developed a rapid and reproducible method for generating such a model in rats by weekly administration of diethylnitrosamine (DEN) at doses based on body weight (BW). By adjusting the duration of administration of DEN, the animals… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0

Year Published

2010
2010
2013
2013

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(38 citation statements)
references
References 30 publications
1
37
0
Order By: Relevance
“…Several authors have shown that these therapeutic effects can be achieved by inducing the expression of specific genes, such as interferon, bone morphogenetic proteins, superoxide dismutase, SPARC, HNF4a, methaloproteinases, urokinase plasminogen activator or insulin-like growth factor I among others, within the liver. [2][3][4][5][6][7][8][9][10] In most cases, the liver expression of the therapeutic transgene is obtained by using adenoviral vectors, which have a natural tropism for the liver. However, adenoviral vectors do not transduce cirrhotic livers as efficiently as healthy livers.…”
Section: Introductionmentioning
confidence: 99%
“…Several authors have shown that these therapeutic effects can be achieved by inducing the expression of specific genes, such as interferon, bone morphogenetic proteins, superoxide dismutase, SPARC, HNF4a, methaloproteinases, urokinase plasminogen activator or insulin-like growth factor I among others, within the liver. [2][3][4][5][6][7][8][9][10] In most cases, the liver expression of the therapeutic transgene is obtained by using adenoviral vectors, which have a natural tropism for the liver. However, adenoviral vectors do not transduce cirrhotic livers as efficiently as healthy livers.…”
Section: Introductionmentioning
confidence: 99%
“…On day 14 after treatment, tumor volumes were measured as described previously. 30 In panels a and c, the numbers above the bars indicate the percentages of the average tumor volumes relative to those of the PBS control (n ¼ 6 for each group). For statistical difference in tumor volumes, *Po0.05; ***Po0.001, Mann-Whitney U-test, as compared between the indicated groups.…”
Section: Resultsmentioning
confidence: 99%
“…The primary multifocal liver tumor model was established in rats by feeding the animals with diethylnitrosamine following a previously described protocol. 30 The tumor model is harder to treat than the implanted model, so the animals were treated by US four times at 3-day intervals and killed on day 14 so tumor volumes could be measured following a previously described method. 30 For the combined chemotherapy and US treatment experiments, animals received US therapy on days 14, 21, 28 and 35 after tumor inoculation.…”
Section: Animal Experimentsmentioning
confidence: 99%
See 2 more Smart Citations